2020
DOI: 10.1021/acsaem.0c01545
|View full text |Cite
|
Sign up to set email alerts
|

Fused Porphyrin Thin Films as Heterogeneous Visible-Light Active Photocatalysts with Well-Defined Active Metal Sites for Hydrogen Generation

Abstract: Metalloporphyrin-based photocatalysts have attracted great interest due to their high extinction coefficient in the visible range coupled to a catalytically active central metal ion surrounded by a highly conjugated heterocyclic macrocycle. In this work, fused copper(II) porphyrin-based conjugated polymer thin films are shown to be active electrocatalysts and photocatalysts for the heterogeneous hydrogen evolution reaction (HER). The fused copper(II) porphyrin thin films notably show a significant reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 42 publications
3
40
0
Order By: Relevance
“…They have been used in applications involving non‐linear optic materials, molecular wires, and supramolecular chemistry [23,24] . Nonetheless, fused porphyrins, and related porphyrinoids featuring extended conjugation, have not been as extensively studied for applications in electrocatalysis [25,26] . Further, although there are reported examples of doubly‐ and triply‐fused dimers, trimers, and oligomeric porphyrin arrays containing Mg, [27] Co, [28] Ni, [22,29–42] Cu, [34–36,38–40,43–47] Zn, [28,30,31,36,38–40,44,45,47–57] Ru, [58] Pd, [29,34–36,38,50] Ag, [46] Pb, [57] Y, [59] and Tb, [59] analogous multinuclear Fe fused porphyrin complexes, which could be useful for applications in electrocatalysis, have yet to be reported.…”
Section: Figurementioning
confidence: 99%
“…They have been used in applications involving non‐linear optic materials, molecular wires, and supramolecular chemistry [23,24] . Nonetheless, fused porphyrins, and related porphyrinoids featuring extended conjugation, have not been as extensively studied for applications in electrocatalysis [25,26] . Further, although there are reported examples of doubly‐ and triply‐fused dimers, trimers, and oligomeric porphyrin arrays containing Mg, [27] Co, [28] Ni, [22,29–42] Cu, [34–36,38–40,43–47] Zn, [28,30,31,36,38–40,44,45,47–57] Ru, [58] Pd, [29,34–36,38,50] Ag, [46] Pb, [57] Y, [59] and Tb, [59] analogous multinuclear Fe fused porphyrin complexes, which could be useful for applications in electrocatalysis, have yet to be reported.…”
Section: Figurementioning
confidence: 99%
“…8 Directly fused porphyrin assemblies are also active catalysts. 14,15 In particular, bimetallic copper(II)-fused porphyrin dimers were shown to be a highly active HER catalyst, demonstrating the direct fusion of the porphyrin macrocycles to be a promising strategy for enhanced electrocatalyst design. 14 More recently, electrochemical and spectroscopic investigations on fused iron(III) porphyrin complexes revealed their ability to store up to six electrons, added to the capability of the p-extended ligand to delocalize electrons across the multimetallic scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…20 Preliminary studies carried out by our group on the electro-and photocatalytic activity of directly fused copper(II) porphyrin conjugated polymer thin films for the heterogeneous HER showed that the phenyl substituent, enabling intramolecular cyclization, promotes superior catalytic performance over the mesityl substituent. 15 Besides the dehydrogenative intermolecular coupling (polymerization) forming triple, double or single linkages between the porphyrin units and the dehydrogenative intramolecular coupling (cyclization), other side reactions can take place during the oCVD reaction of porphyrins. Namely, the chlorination of the macrocycle and the substituents, the demetallation and potential re-metalation of the porphyrin core, and oxidation of the central metal cation can take place (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent publications from Boscher and co-workers reported on a doubly fused Cu(II)-containing porphyrin thin film which was shown to be an active electrocatalysts and photocatalysts towards heterogeneous HER. [47] The fused porphyrin thin films notably reduced the overpotential for HER in comparison to the respective nonfused porphyrin thin films suggesting efficient separation and storage of multiple charges due to extension of π-electron conjugation. Further studies involving different substituents at the peripheral position (phenyl and mesityl) of the fused porphyrin suggested influence of functional groups on the superior catalytic activity of the bis-metalloporphyrin thin films.…”
Section: Electrocatalytic and Photocatalytic Proton Reductionmentioning
confidence: 97%